2013
DOI: 10.1002/srin.201300086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold Deformation and Aging Process on Precipitation Behavior and Mechanical Properties of Fe–18Cr–18Mn–0.63N High‐Nitrogen Austenitic Stainless Steel

Abstract: Effects of different treatments (solid solution + cold deformation + aging condition) on the microstructure of Fe–18Cr–18Mn–0.63N high‐nitrogen austenitic stainless steel and consequently on its mechanical properties were investigated by microscopic observations and mechanical characterizations. For un‐cold‐deformed and 20% cold‐deformed steels, the results show that, all precipitates are Cr2N phase and the granular precipitates transform into cellular precipitates with increasing aging time. However, in 50% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…The present study was carried out to explain the increase in hardness observed when annealing is applied to a cold-worked high-N stainless steel. This increase is opposite to what was previously observed on austenitic high N stainless steels, as reported before [ 23 , 24 ]. Using complementary techniques, such as chemical analyses, EBSD mapping and MET examination, allows explaining how and why hardness increases with annealing.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study was carried out to explain the increase in hardness observed when annealing is applied to a cold-worked high-N stainless steel. This increase is opposite to what was previously observed on austenitic high N stainless steels, as reported before [ 23 , 24 ]. Using complementary techniques, such as chemical analyses, EBSD mapping and MET examination, allows explaining how and why hardness increases with annealing.…”
Section: Discussioncontrasting
confidence: 99%
“…After annealing for 24h between 500 °C to 1050 °C, it was observed that the strengths decrease with the increase in temperature. For a Fe–18Cr–18Mn–0.63N–0.06C steel, cold-worked up to 50%, and then aged at 850 °C, a decrease in room temperature tensile yield and ultimate strengths when ageing time increased is also recorded by Feng et al [ 24 ]. On Fe–18Cr–19Mn–0.9N–0.06C, Vanderschaeve et al [ 25 ] also extensively studied the effect of annealing on a non-cold worked sample for temperatures between 400 °C to 900 °C.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…During the sintering, some of the N atoms dissolve into the austenite matrix, while the others combine with chromium to be precipitated at grain boundaries. [22,23]. Thus, the strength of the samples sintered in N 2 is much higher.…”
Section: The Sample Sintered Inmentioning
confidence: 97%